The Sufi doctrine of man : ?adr al-Din al-Qunawi's metaphysical anthropology - Todd, Richard, 1968- (Islamic Philosophy, Theology and Science. Texts and Studies, 2014)
In The Sufi Doctrine of Man , Richard Todd examines the life and thought of Ibn 'Arabī's chief disciple, Ṣadr al-Dīn al-Qūnawī (13th century C.E.). Making use of manuscript sources, he analyzes and contextualizes Qūnawī's esoteric vision of the nature and purpose of human existence, a doctrine which incorporates core elements of Qūnawī's metaphysics, cosmology, psychology, and eschatology. Qūnawī's thought is placed in relation to Ibn 'Arabī's and that of the Ikhwān al-Ṣafā', and his interaction with the Avicennian tradition is explored by focusing on his dialogue with the philosopher al-Ṭūsī. Although not as famous as his master, Qūnawī is shown to have been a sophisticated metaphysician in his own right, who had a major impact on Sufi thought.